In-situ patch budding for better establishment of bael in rainfed areas - Singh, A K; Singh, Sanjay; Contractor, K.; Makwana, P. (Indian Horticulture, 2019)
The locally available seeds from single genome of bael tree are used for raising the rootstocks. About 8-12 months old seedling of uniform size having similar growth are used as rootstock. The plants propagated through insitu patch budding in May and June ( before onset of rain) with 1-11/2 months old scion shoot is found to be best for multiplication of bael which needs to be popularized for better success and survival of plant under rainfed conditions of western India.